Kegiatan Bermain Literasi untuk Mengembangkan Kemampuan Berbahasa Anak Kelompok A1 di TK Negeri Pembina Bangil - Rifqiyah, Nurul; Arifin, Imron; Sobri, Ahmad Yusuf (Institut Agama Islam Negeri Palangka Raya, 2025)
This study aims to enhance the language skills of 4-5-year-old children through literacy play activities, considering that language learning practices in early childhood education often focus on academics and do not provide sufficient opportunities for exploration and engagement. The study employed a Classroom Action Research (CAR) design based on the Kemmis & McTaggart model, using 17 children in Group A1 at the Pembina Bangil State Kindergarten. Data were collected through observation, documentation, field notes, and interviews, and analyzed descriptively, qualitatively, and in terms of percentage of development. The results showed a significant increase in listening (40%–85%), speaking (25%–80%), letter recognition (30%–85%), and retelling (35%–80%), with the overall average increasing from 33% to 82.5% in cycle II. These findings confirm that literacy play activities effectively stimulate children's language development and are relevant to be applied as a learning strategy in line with the principles of developmentally appropriate practice in early childhood education.